2018
DOI: 10.1590/s2175-97902018000217183
|View full text |Cite
|
Sign up to set email alerts
|

A pH-responsive drug delivery matrix from an interpolyelectrolyte complex: preparation and pharmacotechnical properties

Abstract: Interpolyelectrolyte complexes, which constitute a type of polymeric material obtained through the selfassembly of oppositely charged polymers, exhibit interesting properties for use in the design of smart matrices for drug delivery. In the present study, a stoichiometric interpolyelectrolyte complex (SIPEC) composed of Eudragit E® and Eudragit® L100 was obtained at pH 6.0 and characterized and evaluated as a hydrophilic matrix for dexibuprofen. The formation of a SIPEC was monitored by ζ-potential measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…As an example, the potentiometric titration of the EE used in this study showed that it contained 3.605 mmol/g of the critical dimethylaminoethyl functional group. However, commercial EE has been reported to contain variable levels of this amino group, ranging from 2.86 to 4.28 mmol/g [ 19 ], and one group has reported an even higher level of 5.6 mmol/g [ 20 ]. Thus, FTM-MCR could have different component ratios depending on the property of the EE used.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, the potentiometric titration of the EE used in this study showed that it contained 3.605 mmol/g of the critical dimethylaminoethyl functional group. However, commercial EE has been reported to contain variable levels of this amino group, ranging from 2.86 to 4.28 mmol/g [ 19 ], and one group has reported an even higher level of 5.6 mmol/g [ 20 ]. Thus, FTM-MCR could have different component ratios depending on the property of the EE used.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring of the microenvironmental structural alterations of the new matrices during swelling in the simulated gastrointestinal fluids showed that all IPECs could potentially be used as pH-sensitive carriers because of structural and compositional transformations [ 110 ]. Additionally, Montaña et al [ 119 ] successfully developed the same interpolyelectrolyte complex and investigated the ability of using it as a controlled release matrix for dexibuprofen. The results of the DSC thermograms revealed the presence of a single Tg at 80 °C, indicative of the miscibility of the polymers due to electrostatic interactions, while SEM images confirmed the amorphous state of the complex.…”
Section: Modified Polyelectrolyte Matricesmentioning
confidence: 99%
“… SEM images of ( A ) amorphous Eudragit EPO, ( B ) spherical Eudragit L100, ( C ) amorphous stoichiometric IPEC of EPO/L100. (Adapted with permission from [ 119 ], Scientific Electronic Library Online, Brazil, 2018). …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…First, a vast majority of APIs exhibit poor powder flow properties that restrict their processability and maximum loading in the final dosage form. Second, a significant fraction of commercial APIs and those in discovery pipelines are hydrophobic, which limits their oral bioavailability in vivo. Both powder flow and bioavailability of solid API are governed by the interplay of their critical quality attributes including particle morphology, size, , and solid-state. ,, Co-processing APIs with excipients is a promising particle engineering technique to gain control over these critical attributes and manifest superior API performance. Excipients, although non-therapeutic, play an indispensable role in oral dosage by serving as matrices to control drug loading, , solid-state outcomes, , and tune drug release. , With the APIs being exposed to varied pH conditionshighly acidic in the stomach (1–3) to physiological values (6–7.5) in the saliva and intestinesacross the gastrointestinal tract, the use of pH-responsive excipients to modulate their release has gained significant traction in the last two decades . Eudragit E100, belonging to a class of polymethacrylate-based copolymers, is one such widely used excipient with solubility in gastric fluid up to pH 5. E100 is reportedly non-toxic and is utilized for modulating drug release and taste masking ,,,, in pharmaceutical formulations either on its own or in combination with other Eudragit , and non-Eudragit polymers. , The traditional utility of E100, however, has been heavily limited to generating amorphous solid dispersions by inhibiting precipit...…”
Section: Introductionmentioning
confidence: 99%